2017
DOI: 10.29252/ijrm.15.5.305
|View full text |Cite
|
Sign up to set email alerts
|

Relative frequency of human papillomavirus genotypes and related sociodemographic characteristics in women referred to a general hospital in Tehran, 2014- 2015: A cross-sectional study

Abstract: Background:Human papilloma virus (HPV) is one of the major public health problems and the main causes of cervical cancer. The prevalence HPV infection in developing countries with low financial resources is high. Objective:This study aimed to determine the relative frequency of HPV genotypes and its sociodemographic characteristics in women referred to a general hospital in Tehran, Iran from 2014-2015.Materials and Methods:This cross-sectional study was performed in 400 women with Pap smear samples, referring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…These phenomena might be caused by polluted hookah devices or microbe contaminated water lters. The similar observation of hookah and papillomavirus infection relationship had been reported by some epidemiological studies 18,19 , but still lack of omicsbased analysis for exploring the mechanisms. Among the DEGs obtained here, we observed that CCND1…”
Section: Hisbim For Analyzing the Mechanisms Of Hookah Smokingsupporting
confidence: 74%
“…These phenomena might be caused by polluted hookah devices or microbe contaminated water lters. The similar observation of hookah and papillomavirus infection relationship had been reported by some epidemiological studies 18,19 , but still lack of omicsbased analysis for exploring the mechanisms. Among the DEGs obtained here, we observed that CCND1…”
Section: Hisbim For Analyzing the Mechanisms Of Hookah Smokingsupporting
confidence: 74%
“…One study that was inconsistent with our findings reported that HPV-infected women had no difference in their sex life before and after diagnosis. 36 Although premarital sex is unacceptable in our society, some single women in our study had sex. This is one of the strengths of our study.…”
Section: Discussionmentioning
confidence: 72%
“…One study that was inconsistent with our findings reported that HPV-infected women had no difference in their sex life before and after diagnosis. 36 …”
Section: Discussionmentioning
confidence: 99%
“…In other studies, genotypes 31, 35, 39, 53, and 58 have been reported, in addition to genotype 16. 2 , 18 , 23 , 24 , 28 These differences in the HPV genotype distribution indicate the divergence of HPV prevalence in differing areas. 29 …”
Section: Discussionmentioning
confidence: 99%